The Effectiveness of Salvadora persica (miswak) on Periodontal Health, Literature Review - Ersa, Savana; Ervina, Irma (Journal of Syiah Kuala Dentistry Society, 2024)
Periodontal disease is a global prevalent burden on well-being and health-related quality of life. Adequate plaque control on a daily routine basis is the most critical thing to achieve periodontal health. Using toothbrushes in combination with dentifrices is one of the most common methods of oral hygiene maintenance. However, natural chewing sticks such as Salvadora persica are still used in many developing countries due to their low cost and religious background. Salvadora persica displays precious biotherapeutics capacity for antimicrobial, antiviral, antioxidant, and anti-inflammatory effects. Recently, a lot of Salvadora persica extract has been found in dentifrices, mouthwash, chewing Gum, and even local delivery drugs such as periodontal chips, which are still in the research stage.The present review aims to summarize the evidence of various pharmacological and therapeutic aspects of the effectiveness of Salvadora persica in promoting periodontal health and the treatment of periodontal disease.